Fibre laser cutting of thick closed cell aluminium foam: morphological analysis and its parametric optimisation. (9th July 2019) - Raza, Mohammad Shahid; Datta, Susmita; Singh, Jogender; Saha, Partha
Laser cutting of 10 mm thick closed cell aluminium foam was performed using a 2 kW fibre laser. The parameters selected were laser power (1, 350 W-1, 750 W), scan speed (400 mm/min-1, 000 mm/min) and gas pressure (6-8 bar). The kerf quality (kerf width and taper percentage) was assessed by SEM and optical microscopic images. Laser power and scan speed were found to be the most influencing parameters for good kerf quality. SEM images indicate that the dross attachment is higher at the bottom surface than that at the top surface. Parametric optimisation of the kerf width and taper percentage was carried out using response surface methodology (RSM) technique. Regression analysis was performed to correlate input and output parameters in order to apprehend the significance of these parameters. Finally, it was observed that the model was adequate to predict the variability in the response variables at a confidence level of 95%.